Upper-limb prosthetic maintenance data: A retrospective analysis study - Nagaraja, VH; Cheng, R; Slater, DH; Thompson, MS; Bergmann, JHM (Lippincott, Williams & Wilkins, 2021)
Introduction Understanding repair patterns of upper-limb (UL) prosthetic devices have received little attention compared with their lower-limb counterparts. This study focuses on a retrospective analysis of anonymized UL prosthetic maintenance data to establish if there were any patterns of repairs at a regional prosthetic limb-fitting center in the United Kingdom. A secondary aim of this study is to describe the patient demographics of this center. Methods Data containing prosthetic repair log and demographic description (n = 212) were acquired through our clinical partners and subjected to statistical analyses. Results On average, each client visited the center 0.2 times/year for a new device and 0.9 times/year for maintenance-related activities. It is found that the repair rates are generally higher for body-powered devices (1.28 visits/device per year) compared with passive (0.94 visits/device per year) and externally powered devices (0.90 visits/device per year). In keeping with the typical UK UL-deficient population, there is a high male-to-female ratio, and higher instances of traumatic amputations were noticed for males at the center. There is a very high preponderance of congenital cases and an overall emphasis on prescribing passive devices to a majority of patients at the center. Conclusions The data from our study are similar to previously published data from other centers and show a consistent pattern in terms of relative rates of maintenance attendances for different types of UL prostheses. Clinical Relevance This study provides a longitudinal perspective and insights on ever-changing requirements (prostheses and related care) of the users at the level of a regional limb-fitting center. This study underscores current gaps in prosthetic device durability/reliability and opens up avenues for improvement of prosthetic services and devices.